2010
DOI: 10.1097/sla.0b013e3181c3bcca
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Topical Hemostatic Agents

Abstract: Since ancient times we have attempted to facilitate hemostasis by application of topical agents. In the last decade, the number of different effective hemostatic agents has increased drastically. In order for the modern surgeon to successfully choose the right agent at the right time, it is essential to understand the mechanism of action, efficacy and possible adverse events as they relate to each agent. In this article we provide a comprehensive review of the most commonly used hemostatic agents, subcategoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
369
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(385 citation statements)
references
References 70 publications
5
369
0
11
Order By: Relevance
“…Bone wax, which comprises a mixture of beeswax and emollients such as paraffin, is often used to prevent bleeding from exposed spongy bone following median sternotomy. The wax is not absorbed by the body but, as for any implanted foreign material, may induce a number of side effects including acting as a niche for infections, thereby increasing susceptibility to mediastinitis 11 . Bone wax has been associated with intense inflammatory reactions even years after the performance of a surgical procedure 12 , hence the product could interfere in the uptake of the radiopharmaceutical.…”
Section: Assaymentioning
confidence: 99%
“…Bone wax, which comprises a mixture of beeswax and emollients such as paraffin, is often used to prevent bleeding from exposed spongy bone following median sternotomy. The wax is not absorbed by the body but, as for any implanted foreign material, may induce a number of side effects including acting as a niche for infections, thereby increasing susceptibility to mediastinitis 11 . Bone wax has been associated with intense inflammatory reactions even years after the performance of a surgical procedure 12 , hence the product could interfere in the uptake of the radiopharmaceutical.…”
Section: Assaymentioning
confidence: 99%
“…26,31 Topical hemostatic agents contain active ingredients such as thrombin, fibrinogen, collagen, gelatin, and cellulose and act by promoting coagulation at the site of application and/or physical blockade and tamponade of bleeding vessels. 45 Alternatively, systemic agents to promote hemostasis are available. Lysine analogues (tranexamic acid and epsilon aminocaproic acid) are the most commonly used antifibrinolytic agents, which act by inhibiting plasmin and preserving blood clots formed at sites of bleeding.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Only few cases of paraplegia following the use of oxidized cellulose in thoracic surgery had been reported till 1999 [2,[6][7][8][9]. We present to you a case report of a post-operative iatrogenic acute-onset complete paraplegia due to oxidized cellulose which was completely reversed by a timely re-exploration and thus, no resultant long-term sequelae.…”
Section: Surgicel (Oxidized Cellulose) Original Absorbable Hemostat (mentioning
confidence: 79%
“…But still, even today, it is frequently left in situ. Studies have indicated that the extent of damage is timedependent and the delayed evacuation contributes to the lack of neurological recovery [2,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation